Procedural Multimedia Presentations: The Effects of Working Memory and Task Complexity on Instruction Time and Assembly Accuracy - Irrazabal, Natalia Carolina (2016)
Procedural text conveys information of a series of steps to be performed. This study examined the role of verbal and visuo‐spatial WM in comprehension and execution of assembly instructions, as a function of format (text, images, multimedia) and task complexity (three or five steps). One hundred and eight participants read and executed 27 instructions to assemble a LEGOTM object, in single and dual task conditions. Study times and errors during assembly were measured. Participants processed faster pictorial and multimedia instructions than text instructions, and made fewer errors in the execution of multimedia instructions. Dual task affected more text or picture‐only, than multimedia presentation. A verbal secondary task caused more errors in text or picture‐only presentations, and spatial secondary task also caused interference in text‐only instructions. Overall, these results support the multimedia advantage, and the role of both verbal and visuo‐spatial WM, when understanding instructions.